Tuberculin manufacturing source and breakdown incidence rate of bovine tuberculosis in British cattle, 2005–2009. (26th January 2013) - Downs, S. H.; Clifton‐Hadley, R. S.; Upton, P. A.; Milne, I. C.; Ely, E. R.; Gopal, R.; Goodchild, A. V.; Sayers, A. R.
Abstract : The single intradermal comparative cervical tuberculin (SICCT) test is the primary test used for surveillance for bovine tuberculosis (bTB) in cattle in Great Britain (GB). The tuberculin used can, with other factors, influence test accuracy. In this analysis, the detection of infected cattle in GB 2005–2009 was compared between SICCT tests using tuberculins manufacturered by different manufacturers. Higher rates of reactors (adjusted rate 209 vs 186 per 100, 000 tests, P = 0.003) and herd bTB incidents (adjusted total breakdown rate 5.1 vs 4.5 per 100 herd‐years at risk, P < 0.001) were detected using tuberculin manufactured at Weybridge compared with Lelystad. However, confirmation of infection in reactors by postmortem evidence was higher with Lelystad tuberculin (adjusted percent 44.1 vs 47.1, P = 0.018). The findings, overall, suggest slightly higher test sensitivity and lower test specificity associated with Weybridge tuberculin compared with Lelystad. Assuming effective adjustment for confounding, the overall impact of tuberculin manufacturing source (2007–2009), was calculated to range somewhere between 315 false positive breakdowns, and 1086 bTB breakdowns missed (624 confirmed) as a result of using Weybridge and Lelystad tuberculin, respectively. However, animals that tested negative to the SICCT were not slaughtered at the time of the tests, so definitive conclusions are not possible.